2006
DOI: 10.2307/25065639
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Salicornioideae (Chenopodiaceae): diversification, biogeography, and evolutionary trends in leaf and flower morphology

Abstract: Chenopodiaceae‐Salicornioideae (14–16 gen./c. 90 spp.) are distributed worldwide in coastal and inland saline habitats. Most of them are easy to recognize by their succulent‐articulated stem with strongly reduced leaves and by flowers aggregated in dense, thick spike‐shaped thyrses. ITS and the atpB‐rbcL spacer were sequenced for 67 species representing 14 genera of Salicornioideae and analysed with maximum parsimony and maximum likelihood, a fossil‐calibrated molecular clock using the penalized likelihood met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
150
2
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(166 citation statements)
references
References 53 publications
8
150
2
6
Order By: Relevance
“…Kadereit and co-workers have analyzed diversification, biogeography and evolutionary trends in leaf and flower morphology of Salicornioideae and Chenopodioideae. About 90 species have been described occurring worldwide in coastal and saline habitats (Kadereit et al, 2006). Using maximum parsimony and maximum likelihood, a fossil-calibrated molecular clock and lineage through time plots, it was demonstrated that the monophyletic Salicornioideae originated in Eurasia along the northern margin of the Tethys Sea during the Late Eocene and Early Oligocene (38.2-28.7 Mya, Table 2, Kadereit et al, 2006) and experienced a rapid radiation into its major lineages during the Early Oligocene.…”
Section: Molecular Phylogeny Palaeoclimate Diversification and Biogmentioning
confidence: 99%
See 2 more Smart Citations
“…Kadereit and co-workers have analyzed diversification, biogeography and evolutionary trends in leaf and flower morphology of Salicornioideae and Chenopodioideae. About 90 species have been described occurring worldwide in coastal and saline habitats (Kadereit et al, 2006). Using maximum parsimony and maximum likelihood, a fossil-calibrated molecular clock and lineage through time plots, it was demonstrated that the monophyletic Salicornioideae originated in Eurasia along the northern margin of the Tethys Sea during the Late Eocene and Early Oligocene (38.2-28.7 Mya, Table 2, Kadereit et al, 2006) and experienced a rapid radiation into its major lineages during the Early Oligocene.…”
Section: Molecular Phylogeny Palaeoclimate Diversification and Biogmentioning
confidence: 99%
“…About 90 species have been described occurring worldwide in coastal and saline habitats (Kadereit et al, 2006). Using maximum parsimony and maximum likelihood, a fossil-calibrated molecular clock and lineage through time plots, it was demonstrated that the monophyletic Salicornioideae originated in Eurasia along the northern margin of the Tethys Sea during the Late Eocene and Early Oligocene (38.2-28.7 Mya, Table 2, Kadereit et al, 2006) and experienced a rapid radiation into its major lineages during the Early Oligocene. This was after the end of warm humid period of the Middle Palaeocene to Early Eocene and the start of a long period of decreasing temperatures and increasing aridity (Willis and McElwain, 2002).…”
Section: Molecular Phylogeny Palaeoclimate Diversification and Biogmentioning
confidence: 99%
See 1 more Smart Citation
“…Scott (Amaranthaceae) is a markedly complex genus as has been reported by many authors (Castroviejo & Coello, 1980;Castroviejo & Lago, 1992;Shepherd & Yan, 2003;Kadereit & al., 2006;Alonso & Crespo, 2008), and a large number of synonyms is recognized due to its taxonomical difficulty (Maire & Quézel, 1962;Quézel & Santa, 1963;Meikle, 1977;Pignatti, 1982;Bolòs & Vigo, 1990;Ball, 1993;Coste, 2007;Guilló & al., 2011). The marked halophytic behaviour of Sarcocornia species favours the development of similar morphological traits, which makes quite difficult to distinguish species, and even other related genera (e.g.…”
Section: Introductionmentioning
confidence: 76%
“…At least xerohalophytic taxa have a well-founded claim to succulence. Stem succulence is either cortical (with an outer palisade-like layer, and a central water-storage parenchyma; Fahn & Cutler, 1992), or derived from sheathing leaf bases ("false" stem succulence) (Kadereit et al, 2006). Weakly expressed leaf succulence is common, and in terete leaves (e.g.…”
Section: No Tes O N Selec Ted Familiesmentioning
confidence: 99%